Improving Student Learning Outcomes Through The Think Pair and Share Model In Learning English - Nadwah, St. (Universitas Negeri Makassar, 2022)
The Think Pair and Share cooperative learning model is a “cooperative learning model that was first developed by Frank Lyman and his colleagues at the University of Maryland in 1981. This research is a classroom action research. The research subjects are students in grades 8-2 of SMP Negeri 2 Sengkang a total of 16 people consisting of 8 men and 8 women. The total number of students in grades 8-2 is 36 people. While the research procedure consists of 4 stages, namely: planning, implementation, observation, and reflection. Furthermore, data analysis was carried out through three stages, namely data reduction, data presentation, and data verification/conclusion. The results of the study indicate that the Think Pair and Share Model can improve learning outcomes in English learning for grades 8-2 of SMP Negeri 2 Sengkang in the 2021/2022 academic year.